Current management of transition of young people affected by rare renal conditions in the ERKNet - Kreuzer, Martin; Schaefer, Franz (European journal of human genetics, 2019)
Transition in medical care is a high-risk period in adolescence and young adulthood. To date, data on transition policy, its application in practice, and transition procedures in patients with rare, hereditary kidney diseases in Europe is scarce. An online survey was developed and was distributed within the paediatric centres of the European Reference Network for Rare Kidney Diseases (ERKNet) aiming to assess the transition-relevant structures from the providers’ perspectives. Its items were based on the consensus statement on transition published by the International Society of Nephrology (ISN) and the International Paediatric Nephrology Association (IPNA) in 2011. Forty-six paediatric experts based at 28/32 ERKNet university hospitals participated. Annually, a median number of 14 patients (1-80) are transferred to adult based care. One centre continued to care for paediatric kidney transplant recipients throughout their entire lifespan. Choosing this option terminated the survey and no further data was obtained from this centre. 29/45 experts confirmed the application of an—at least unwritten—transition procedure (64%). Transition clinics are offered by 23 experts. Most physicians (40%) transfer patients at age 18-19, 10 experts at age <18. Most physicians transfer the patients to a university hospital and/or a community hospital. The transition guidelines have been implemented in ERKNet centres only partly and with huge heterogeneity. Implementation of transition tools and structures within ERKNet could improve health of children with hereditary kidney diseases. Adherence of experts to the transition-guidelines was significantly correlated with gross national income of their countries.
Gesehen am 13.02.2020